ICT-Based Islamic Religious Education Learning Design to Improve Student Motivation and Learning Outcomes in the Digital Era - Yusuf Bintang Tri Sakti; Winda Ayu Dyah Saputri (JISEI: Journal of Islamic Studies and Educational Innovation, 2026)
Digital transformation in education demands innovative Islamic Religious Education learning that adapts to the characteristics of digital era learners. This research explores ICT-based Islamic education instructional design to enhance students' motivation and learning outcomes through qualitative methods with literature review approach analyzing scientific publications from 2021-2025. Research findings indicate that ICT-based Islamic education instructional design integrating audiovisual multimedia teaching materials, digital learning platforms, and multimodal learning strategies effectively increases student learning motivation up to more than eighty percent and improves learning outcomes with moderate to high N-Gain category. Students' perceptions toward ICT-based Islamic education learning are highly positive with strong responses on visual aspects, ease of use, and active engagement. Implementation challenges include infrastructure limitations, teacher digital literacy, and quality content availability requiring optimization strategies through infrastructure development, continuous teacher training, and wise technology utilization policies to develop technologically competent Muslim generations with strong spiritual foundations.